Makna Tu’u Belis bagi Masyarakat Kelurahan Mokdale Kecamatan Lobalain Kabupaten Rote Ndao - Christy Pratiwi Magdalena Fanda; Lukas L. Daga; Syamsuriadi Syamsuriadi (Universitas Nusa Cendana, 2018)
The culture of each region varies both arts, home form, the procedure of marriage and other social traditions, this shows a multi-cultural society. This difference becomes own peculiarities for Mokdale village society. Mokdale village society has a distinctive tradition, that is Tu'u Belis tradition, this tradition is a tradition practiced by generations as it has its own value and meaning in social life. This study aims to determine the meaning Tu'u Mokdale Belis for the village society. The study was conducted in the village of Mokdale. Informan in this research is the general public who were four people with two criteria of the traditional leaders and the two society leaders. Data for this study were obtained from the results of observations, interviews, documentary studies and analyzed descriptively qualitative. The results showed that the meaning Tu'u Mokdale Belis for the village society is to strengthen the relations between familial and kinship as well as ease the burden in the payment of bride price. Tu'u Belis deemed to have solidarity value in establishing kinship systems such as mutual help among men’s family in terms of fund-raising to pay the magnitude bride price on the part of Women. This will take place on a reciprocal basis. Tu'u Belis traditions have also been associated with symbolic interaction theory, this is shown by the interaction between the groom's family and the local society and in the implementation, Tu'u Belistradition becoming the socialization process from of generation to generation by the individual to the society.